2020
DOI: 10.1080/13545701.2020.1786594
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Medium-Term Effects of Informal Eldercare on Labor Market Outcomes

Abstract: Informal caregivers, often family members, provide valuable services to elderly persons with long-term care needs. However, the time commitment of caregiving often competes against time spent in the labor force. In addition to the momentary trade-off, long-term consequences are possible since older workers in particular might find it difficult to reenter the labor market after a period of caregiving. While several studies document a negative relationship between caregiving and paid work, little is known about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
0
12
1
Order By: Relevance
“…Across Europe, most working age informal carers combine care with part-time work, and research indicates that older women are less often employed regardless of the intensity of care they provide [ 18 ]. Findings from studies in other European countries indicate that informal care has a negative impact on carers’ employment, with younger women who provide more care in risk of lower income due to reduced working hours [ 18 , 66 ]. Meanwhile, several international studies show that female WKCs are more prone to reduce and limit their participation in paid work compared to men [ 2 , 33 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Across Europe, most working age informal carers combine care with part-time work, and research indicates that older women are less often employed regardless of the intensity of care they provide [ 18 ]. Findings from studies in other European countries indicate that informal care has a negative impact on carers’ employment, with younger women who provide more care in risk of lower income due to reduced working hours [ 18 , 66 ]. Meanwhile, several international studies show that female WKCs are more prone to reduce and limit their participation in paid work compared to men [ 2 , 33 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Any caregiving (i.e., at least weekly provision of care) was assessed by 17 studies. 17,36,37,46,47,[51][52][53][54][55][56][57][58][59][60][61][62] The random-effects model (Figure 2) found a signi cant 4.42-percentage-point reduction (95% CI: -0.0662 to -0.0222, p-value=0.0003) in LFP associated with any caregiving. Heterogeneity was high (I 2 =84.4%) and publication bias was ruled out (p-value=0.254).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Nine studies assessed the effect of daily caregiving on men's LFP. 36,37,[54][55][56][57][58][59][60] Using the random-effects model (Figure 3), the reduction in LFP due to daily caregiving was 8.00 percentage points (95% CI: -0.125 to -0.0347) and signi cant (p-value=0.002). Heterogeneity was very high (I 2 =96.3%), but there was no publication bias (p-value=0.459).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…These studies are specifically focused on those situations where individuals both work outside the home and are responsible for the care of elderly or disabled people within it. A study into the provision of elder care was recently undertaken by Heger and Korfhage (2020), analyzing the situation of informal caregivers responsible for the provision of long-term care for older family members. The study found that time spent on caregiving often competes with the time spent on paid work, making it difficult for older caregivers to re-enter the labor market after a period of caregiving.…”
Section: Job Flexibility Within Organizationsmentioning
confidence: 99%